Pragmática da comunicação no Exército: estudo sobre interações em um grupo de WhatsApp organizacional, sob a perspectiva da Escola de Palo Alto - Melo, Dealessandro David Lima de (2018)
The object of study of this research is the WhatsApp as the stage of interactions in a particular Military Organization of the Brazilian Army. The Palo Alto School triggers reflections linked to a systemic view of phenomena, leading, therefore, to an interactive analysis of the organization and of these phenomena that coexist in it. These systems are composed of the aggregation of behaviors in constant interaction that influence the image of the organization. The emergence of the WhatsApp application marked new opportunities for organizational communication in organizations, and the military environment is embedded in this global trend, also suffering the influence of all the peculiarities of this new technology in the Austin Speech Acts (1990). Its problematic in which the study is inserted is that the interactions in the organization reached instantaneous levels of great amplitude with the insertion of a collective group of WhatsApp, making an incessant production of senses in network, where the redundancy of the behaviors can or not contribute to communicational stability in a group of people. The study employs the theoretical reference of Watzlawick (1993), Duterme (2002) and Austin (1990). It also understands the organizational environment by Morgan's culture metaphor (2002). In the development of the exploratory research, the behaviors resulting from communication through a WhatsApp group with more than 100 professionals were observed in their ability to reduce or not the instability in communication among the professionals of a military network organization. The research was done through a content analysis of an internal and institutional group of WhatsApp, seeking the logic of interactions to reduce uncertainties in the organization.